PHYSICAL EDUCATORS'S KNOWLEDGE ABOUT FIBROMYALGIA (Fiep Bulletin - online, 2011)
The main purpose of this descriptive field research was to evaluate physical education professionals knowledge about fibromyalgia, it hypothetic causes, possible symptoms and treatment ways. The sample was formed by 30 Florianópolis (SC) physical education professionals, with random selection. They presented mean 30,6 ± 6 years old, with 63,3% male and 36,7% female; 73,3% are licensed 26,7% are bachelors, and 40% graduated, 53,3% post graduated and just 6,7% of masters. According with the time they are formed, 36,7% of them are until 3 years, 36,7% are between 4 and 7 years and 26,7% are up to 8 years. Though these professionals the main have or had been worked with health, sports or/and education. A questionnaire was used as a research instrument. To statistics analysis was used descriptive statistic. 48,9% ± 19,7 was bull eyes mean on the question realized. We had been percept that physical education professionals' knowledge was moderate about fibromyalgia, as well as significant variation of knowledge between professionals about this syndrome.
Keywords: physical education professionals; fibromyalgia; knowledge